Distribution of clams Meretrix casta (Chemnitz) in the Sadras backwaters - Ramgopal, S; Nair, K V K; Azariah, Jayapaul (Indian Journal of Fisheries, 2011)
Resource potential of clams was studied from February 1988 to January 1989 in the Sadras backwaters at Kalpakkam. The distribution of clams in the backwaters was not uniform. The biomass of clams varied from 56 to 6416 g/m". Population density varied from 11 to 2066 clams/m*. Population mostly comprised Meretrix casta (81.7 to 96.8%). The spatfall of clams was recorded in May and it continued up to July. The data established that sediment characteristics, rather than hydrographic parameters, greatly influence the distribution of clams in the backwaters